Insulin-like growth factor binding protein 3 promotes radiosensitivity of oral squamous cell carcinoma cells via positive feedback on NF-κB/IL-6/ROS signaling - Wang, Ssu-Han (J Exp Clin Cancer Res, 2021)
BACKGROUND: Ectopic insulin-like growth factor binding protein 3 (IGFBP3) expression has been shown to enhance cell migration and lymph node metastasis of oral squamous cell carcinoma (OSCC) cells. However, OSCC patients with high IGFBP3 expression had improved survival compared with those with low expression. Therefore, we speculated that IGFBP3 expression may play a role in response to conventional OSCC therapies, such as radiotherapy. METHODS: We used in vitro and in vivo analyses to explore IGFBP3-mediated radiosensitivity. Reactive oxygen species (ROS) detection by flow cytometry was used to confirm IGFBP3-mediated ionizing radiation (IR)-induced apoptosis. Geneset enrichment analysis (GSEA) and ingenuity pathway analysis (IPA) were used to analyze the relationship between IGFBP3 and nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) signaling. Assays involving an NF-κB inhibitor, ROS scavenger or interleukin 6 (IL-6) were used to evaluate the NF-κB/IL-6/ROS signaling in IGFBP3-mediated radiosensitivity. RESULTS: Ectopic IGFBP3 expression enhanced IR-induced cell-killing in vitro. In vivo, IGFBP3 reduced tumor growth and increased apoptotic signals of tumor tissues in immunocompromised mice treated with IR. Combined with IR, ectopic IGFBP3 expression induced mitochondria-dependent apoptosis, which was apparent through mitochondrial destruction and increased ROS production. Ectopic IGFBP3 expression enhanced NK-κB activation and downstream cytokine expression. After IR exposure, IGFBP3-induced NF-κB activation was inhibited by the ROS scavenger N-acetyl-L-cysteine (NAC). IGFBP3-mediated ROS production was reduced by the NF-κB inhibitor BMS-345541, while exogenous IL-6 rescued the NF-κB-inhibited, IGFBP3-mediated ROS production. CONCLUSIONS: Our data demonstrate that IGFBP3, a potential biomarker for radiosensitivity, promotes IR-mediated OSCC cell death by increasing ROS production through NF-κB activation and cytokine production. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s13046-021-01898-7.